Keilor Historical Society - Keilor Historical Society (Keilor, Vic. : Keilor Historical Society.)
Website of: Keilor Historical Society. Formed in 1988, the aim of the KHS is to promote the history of the region. Contains information such as the history of Keilor including its highlights, list of publications and books available for purchase, and links to other historical societies and cultural institutions.
Title from home page (viewed on Jan. 14, 2008).
Text and graphics.
Mode of access: World Wide Web
Selected for archiving
Keywords: Keilor Historical Society; Keilor (Vic.) -- History